Supplement for Performing contrast analysis in factorial designs: From NHST to confidence intervals and beyond. Educational and Psychological Measurement - Stefan Wiens (Stockholm University, 2017)
Supplementary material for the articleWiens, S., & Nilsson, M. E. (2016). Performing contrast analysis in factorial designs: From NHST to confidence intervals and beyond. Educational and Psychological Measurement, in press. doi: 10.1177/0013164416668950. The full analysis can be found in the article.
Contains R scripts (created with https://www.r-project.org/) and a JASP file (created with JASP software, https://jasp-stats.org/, an alternative to SPSS and R).
Keywords: 170110 Psychological Methodology, Design and Analysis; Psychology; Psykologi